Proportion of pregnant women screened for hypertensive disorders in pregnancy and its associated factors within antenatal clinics of Kinshasa, Democratic Republic of Congo - Dalau Mukadi Nkamba; John Ditekemena; Gilbert Wembodinga; Pierre Bernard; Antoinette Tshefu; Annie Robert (BMC, 2019)
Abstract Background Screening for hypertensive disorders in pregnancy (HDP) is clinically important for identifying women at high risk, and planning early preventative interventions to improve pregnancy outcomes. Several studies in developing countries show that pregnant women are seldom screened for HDP. We conducted a study in Kinshasa, DR Congo, in order to assess the proportion of pregnant women screened for HDP, and to identify factors associated with the screening. Methods We conducted a facility-based cross-sectional study in a random sample of 580 pregnant women attending the first antenatal visit. Data collection consisted of a review of antenatal records, observations at the antenatal care services, and interviews. A pregnant woman was considered as screened for HDP if she had received the tree following services: blood pressure measurement, urine testing for proteinuria, and HDP risk assessment. Multivariable logistic regression, with generalized estimating equations, was used to identify factors associated with the screening for HDP. Results Of the 580 pregnant women, 155 (26.7%) were screened for HDP, 555 (95.7%) had their blood pressure checked, 347(59.8%) were assessed for risk factors of HDP, and 156 (26.9%) were tested for proteinuria. After multivariable analysis, screening for HDP was significantly higher in parous women (AOR = 2.09; 95% CI, 1.11-3.99; P = 0.023), in women with a gestational age of at least 20 weeks (AOR = 5.50; 95% CI, 2.86-10.89; P = 0.002), in women attending in a private clinic (AOR = 3.49; 95% CI, 1.07-11.34; P = 0.038), or in a hospital (AOR = 3.24; 95% CI, 1.24-8.47; P = 0.017), and when no additional payment was required for proteinuria testing at the clinic (AOR = 2.39; 95% CI, 1.14-5.02; P = 0.021). Conclusion Our results show that screening for HDP during the first antenatal visit in Kinshasa is not universal. The factors associated with screening included maternal as well as clinics' characteristics. More effort should be made both at maternal and clinic levels to improve the screening for HDP in Kinshasa.